Behaviors, Beliefs, and Recommendations to Optimize Promotion of Safe Fish Consumption Before and During Pregnancy: A Physician Survey - Jeanette Y. Ziegenfuss; Jennifer M. Dinh; Patricia McCann; Abigail S. Katz; Meghan M. JaKa; Jacob Haapala; Cresta Jones; Abbey Mello; Jeremy Springer; Thomas E. Kottke (Journal of Primary Care & Community Health, 2022)
Introduction: Eating fish before and during pregnancy is important but care must be taken to choose fish which maximize developmental outcomes. Physicians, a trusted health information source, could provide this nuanced communication. This cross-sectional survey of a representative sample of 400 family medicine and obstetrics and gynecology (OB-GYN) physicians in Minnesota was designed to understand physician behaviors and beliefs about safe fish consumption, describe barriers to physician-patient conversations about safe fish consumption generally and as part of prenatal care and to identify resources to help facilitate conversations on this topic. Methods: Data was collected January to April 2020. Two hundred nineteen surveys were completed (55% response rate) with 194 reporting seeing patients at least 1 day a week. Descriptive survey results from all were summarized and analyzed overall and by physician specialty. Responses to 3 open-ended questions were thematically coded to enrich the quantitative results. Results: While 62% of these reported discussing nutrition topics, only about one-third reported discussing with patients the benefits and about one-quarter the risks of eating fish. Despite the relative infrequency of fish discussions, almost all (>90%) respondents agreed that it is important to discuss fish consumption with people who are or may become pregnant. The largest reported barrier to these conversations was time (82%), and the most endorsed resource to overcome identified barriers was talking points (72%). Conclusions: Because physicians report limited time, resources that facilitate fish consumption should be succinct while serving to both nudge the message and direct clinicians and their patients to robust information.